Integrating Adequacy, Equivalence, and Intercultural Communicative Competence in Translation and English Teaching - Subanova Dilafruz Vahapjanovna; Rustamov Firdavs Rafael o‘g‘li; Jumayev Bekzodjon To‘ra o‘g‘li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This paper examines how the concepts of adequacy and equivalence in translation theory intersect with Intercultural Communicative Competence (ICC) in English language teaching. Adequacy focuses on fidelity to source texts, while equivalence emphasizes reproducing intended communicative effects. ICC, meanwhile, addresses learners’ abilities to interpret cultural meanings and communicate effectively across linguistic boundaries. Integrating these approaches, the study highlights theoretical foundations, classroom strategies, and practical implications. Findings suggest that understanding both translation principles and intercultural dynamics enhances language instruction and promotes culturally aware translation practices [1][2][3][4].